Crimson Tide: Hans Zimmer, Subliminal Harmony, and Submerged Voices (Cinéma & Cie. Film and Media Studies Journal, 2025)
Crimson Tide (Tony Scott, 1995) is a signal example of Hollywood action-adventure movies of the past forty years and in particular of the “high-concept” movie. The score by Hans Zimmer is a landmark score for the composer and consolidates his reputation for scoring films of that genre. This article addresses the now-famous Zimmerian work process and several stylistic traits, including the use of a male chorus. Choral voices in the film’s context provide both a synecdochic link to the submariners but also function as a commentative chorus. Using Neo-Riemannian theory, the potential contribution of which to film-music studies is still only now beginning to be explored, I examine the deployment of specific harmonic strategies that create a link back to earlier Hollywood film-music practices and show how Zimmer represents less an evolution than a continuation of recognisable styles and idioms.
Keywords: Corporate Classicism; Hans Zimmer; Choral Voices; Neo-Riemmanian Theory; Narration